Enhancement of the e-SKT system by applying rich internet application (RIA) concept / Anita Daud - Daud, Anita (2009)
UiTM performance appraisal process and procedure follow the guidelines on the implementation of performance assessment for civil services in Malaysia. For this project, the focus is on interface for 'Sasaran Kerja Tahunan' (SKT) which is the key performance appraisal components. The aim for this proposal is to enhance usability interaction design of e-SKT system by applying Rich Internet Application (RIA) concept. The objectives are to identify the features of RIA that could overcome of current e-SKT system, to design e-SKT interface by applying Rich Internet application (RIA) and to demonstrate the one of the Rich Internet application (RIA) concept to the e-SKT system. In addition, the methodology of this research consists of four phases. There are problem identification and planning phase, conceptual study phase, design phase and development phase. This project emphasizes more on the usability of the e SKT system. Finally, the researcher has concluded the project by summarizing the conclusion of the project, limitation and recommendation for future work.